2020
DOI: 10.1001/jamanetworkopen.2020.13929
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Secondary Sarcomas Among Patients With Cancer of the Abdomen or Pelvis Who Received Combinations of Surgery, Radiation, and Chemotherapy vs Surgery Alone

Abstract: Key Points Question What is the rate of secondary sarcoma among patients with nonmetastatic cancer of the prostate, bladder, colon, rectum or anus, cervix, uterus, or testis who were treated with combinations of surgery, radiation, or chemotherapy compared with patients treated with surgery alone and with the general population? Findings In this cohort study of 173 580 patients, the rate of secondary sarcoma among patients treated with radiotherapy was incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Identifying reliable biomarkers for predicting the clinical response to immunotherapy in different malignancies has become an urgent requirement; several studies have demonstrated that chemotherapy and radiotherapy could elevate the incidence of second primary malignancy. [ 9 , 10 ] However, the relationships of immunotherapy with long-term and short-term second primary malignancy incidence are still unclear and require further long-term investigation. Regarding the treatment, we suggested NGS to both patients, but neither accepted the suggestion.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying reliable biomarkers for predicting the clinical response to immunotherapy in different malignancies has become an urgent requirement; several studies have demonstrated that chemotherapy and radiotherapy could elevate the incidence of second primary malignancy. [ 9 , 10 ] However, the relationships of immunotherapy with long-term and short-term second primary malignancy incidence are still unclear and require further long-term investigation. Regarding the treatment, we suggested NGS to both patients, but neither accepted the suggestion.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, while our case predominately examines a genitourinary radiation-induced secondary malignancy in a male patient, both genders are at risk. A cohort of men and women undergoing abdominopelvic radiation for primary colorectal or genitourinary cancers were found to have an incidence of 0.3% developing sarcomas after radiation [11]. In addition, age has been examined as a risk factor for radiation-induced secondary malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…A review of rhabdomyolysis for clinical practice in AKI noted pathophysiologic similarities with tumor lysis syndrome (Chavez et al, 2016). Of relevance, the incidence of secondary sarcomas was higher in patients treated with radiation, surgery, and chemotherapy than with surgery alone, which could be related to dysregulated levels of phosphate released during tumor lysis from radiation and chemotherapy (Hird et al, 2020). A low‐phosphate diet in patients receiving radiation and chemotherapy might help mitigate the risk of phosphate toxicity from tumor lysis syndrome, but more studies are needed in this area.…”
Section: Alcohol and Rhabdomyolysismentioning
confidence: 99%